The Smell of Opium in Minangkabau: Tradition of Betel Chewing and Smoking Tobacco in the 19th Century - Nasir, Muhammad (Regalia Institute, 2023)
One of the historical themes of the Padri movement in Minangkabau in the 19th century was about eradicating the habit of smoking madat that occurred in Minangkabau society. The habit of smoking opium cannot be read at face value without investigating how opium-derived opium is used in the daily habits of the Minangkabau people. For example, in the habit of chewing betel nut and smoking tobacco. Therefore, using a social history approach, this paper will describe how opium is involved in the habit of chewing betel nut and smoking tobacco in the Minangkabau community. Thus, this paper will help explain how to understand the social context of the Padri in eradicating habits that they consider to be behavior that is not in accordance with Islamic teachings.